A review on the solubility enhancement technique for pharmaceutical formulations - Batrisyia, Raja Nurul; Janakiraman, Ashok Kumar Janakiraman; Long, Chiau Ming; Helal Uddin, A.B.M.; Sarker, Zaidul Islam; Liew, Kai Bin (2022)
Abstract Several properties of potential drug molecules such as the solubility of the drug molecule must be determined prior to developing dosage forms as the solubility of a drug molecule is one of the key criteria in achieving an effective drug concentration. Solubility is expressed as the number of parts by volume of solvent necessary to dissolve one part by weight of a solid or one part by volume of a liquid according to pharmacopoeias. Poor water solubility is a critical issue in the formulation development with more than 40% of the novel chemical entities being insoluble in water. Different strategies have been used to enhance the solubility of poorly soluble drugs which include physical and chemical modifications of drug and other methods like particle size reduction, crystal engineering, salt formation, solid dispersion, use of surfactant and so. The properties of a drug, site of absorption, and required dosage form characteristics helps in the selection of solubility enhancing techniques.